High-quality fuel from food waste - investigation of a stepwise process from the perspective of technology development - Yin, Ke (2017)
A stepwise process (SP) was developed for sustainable energy production from food waste (FW). The process comprised of hydrothermal treatment followed by oil upgrading. Synthetic food waste was primarily used as feedstock in the hydrothermal reactor under subcritical water conditions. The produced hydrochars were analyzed for calorific value (17.0–33.7 MJ/kg) and elemental composition indicating high-quality fuel comparable to coal. Hydrothermal carbonization (e.g. 180°C) would be efficient for oil recovery (>90%) from FW, as compared to hydrothermal liquefaction (320°C) whereby lipid degradation may take place. The recovered oil was upgraded to biodiesel in a catalytic refinery process. Selected biodiesels, that is, B3 and B4 were characterized for density (872.7 and 895.5 kg/m3), kinematic viscosity (3.115 and 8.243 cSt), flash and pour point (30°C and >126°C), micro carbon (0.03% and 0.04%), sulfur (both <0.0016%), and calorific value (38,917 and 39,584 J/g), suggesting similar quality to commercial biodiesel. Fatty acid methyl ethers content was further analyzed to assess the influence of hydrothermal treatment in biodiesel quality, indicating the limited impacts. Overall, the SP provides a promising alternative for sustainable energy recovery through high-quality biofuel and hydrochar production.